THE EFFECT OF FAMILY OWNERSHIP, AGENCY COST, ENVIRONMENTAL PERFORMANCE, CORPORATE SOCIAL RESPONSIBILITY ON FIRM VALUE - Putri, Naomi Hansen; Cahyadi, Hadi (International Journal of Application on Economics and Business, 2023)
In today's dynamic and competitive business conditions, companies must be able to adapt and have the ability to compete so that company goals can be achieved. Company goals can be reflected through the ability to increase company value. This study aimed to examine the effect of family ownership, agency costs, environmental performance, and corporate social responsibility on firm value with financial performance as mediation. The population of this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The sample in this study used a purposive sampling method and data analysis techniques using SmartPLS 4.0 by testing the direct and indirect effects between the independent and dependent variables. The results showed that family ownership has a significant effect on firm value, agency costs have a significant effect on firm value, corporate social responsibility has a significant effect on firm value, financial performance has a significant effect on firm value, but environmental performance has no significant effect on firm value. Then, family ownership and corporate social responsibility have no significant effect on financial performance, while agency costs and environmental performance have a significant effect on financial performance. Furthermore, based on research on indirect effects, financial performance does not mediate the influence of family ownership, agency costs, environmental performance, and corporate social responsibility on firm value.